Journalism, democracy, and human rights in Zimbabwe - Mutsvairo, Bruce; Muneri, Cleophas T. (Lanham: Lexington Books, 2020)
"Journalism, Democracy, and Human Rights in Zimbabwe provides an empirical analysis of Zimbabwe's ongoing state of affairs. Bruce Mutsvairo and Cleophas T. Muneri examine the intersection between journalism, democracy, and human rights to historicize and critique past successes and failures that have played out in Zimbabwe's past, as well as interrogate future challenges that await the nation's quest for democratization. The authors examine what role citizen journalists, human rights activists, professional journalists, and social media dissents could potentially play toward ending the country's current adversity. Scholars of journalism, media studies, communication, African studies, and political science will find this book particularly useful"--
Keywords: Political activists; Politics and government; Human rights; Journalism; Zimbabwe